P102: TeamSTEPPS: promoting a culture of safety. (2nd June 2016) - Webb, A.; Lussier, D.; Ngo, M.; Klassen, J.; Steigerwald, R.; Buchel, A.
Abstract : Introduction / Innovation Concept: Adverse events due to medical error are a significant source of preventable morbidity and mortality in Canada's emergency departments. Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) was introduced in 2006 as a strategy to minimize these errors. Although these strategies have been available and widely implemented in hospitals over the last decade, the optimal method of teaching these tools and strategies has not been elucidated.Methods: We endeavoured to introduce a twelve month longitudinal TeamSTEPPS program to physicians, nurses, and allied health care professionals in a busy tertiary care hospital via a multi-pronged approach consisting of group huddles, props in the department, and several social media strategies. Dedicated observers in the emergency department recorded the use of the strategies by staff members to identify improved and sustained use of TeamSTEPPS behaviours after they were introduced.Curriculum, Tool, or Material: The program that consists of five modules to improve patient safety outcomes: Team structure; Leadership; Situation Monitoring; Mutual support; and Communication. Each module consisted of educational tools including posters in the department explaining the concepts, twice weekly department huddles to discuss the importance of the monthly topic and promote team sharing with real life examples, as well as stimulating and generating discussions around the monthly theme on social media (Facebook, Twitter, and an on-line blog). For several modules, extra prompts, such as I PASS the BATON handover cards were also provided to act as reminder visual cues. The first two modules were rolled out with on-line music videos rewritten to promote the significance of the modules. A team performance observation tool was adopted from the TeamSTEPPS program, and behaviors were evaluated and recorded under the five domains.Conclusion: Although unable to detect a meaningful difference in our pre and post-implementation observations, we present a novel approach to educating a multi-disciplinary team about TeamSTEPPS in a busy emergency department, along with the challenges encountered in this unique area of research, and recommendations for further study to interested parties. The TeamSTEPPS program likely could offer as much to the emergency department as similar programs have to the aviation industry yet it requires extensive investigation within this health care venue.